Beyond Literal Understanding of Emotions - Jasielska, Aleksandra (Poznańskie Studia Slawistyczne, 2015)
The meaning of emotions and the meaning of words- emotions’ labels are described in studiem about emotions. Although there are some differences between these two domains, most studies about understanding emotions use lexical approach. On the other hand, the nonspecific limits inspired by language can be noticed in the area of changes in emotion meaning. Two studies were conducted and metaheuristic postulates were involved with the aim of breaking these limits. The denotation and emotional complexity were examined/analyzed in the first study. In the second study the atypical connotations taken from the psychology of creativity were used. The outcomes were discussed in relation to abstraction and metaphor as a result it is possible to go beyond literal understanding of emotions and express emotions verbally.